Between Cointegration and Multicointegration. Modelling Time Series Dynamics by Cumulative Error Correction Models - Marcus Scheiblecker (Austrian Institute of Economic Research (WIFO), 2012)
This paper proposes a cumulative error correction model where the summing weights follow a geometrically decreasing function of prior deviations from equilibrium and are estimated from the data. It is shown that this approach is located in between the traditional error correction model - where no weight is given to deviations from steady state prior to the most recent period - and the error correction model based on the idea of multicointegration. The presented form of accumulation does not change the order of integration of the series, like in the multicointegration approach of Granger and Lee (1989). Based on this model type, the relationship between US private consumption and real disposable income of private households is estimated. The short-run forces setting-off last period's deviations are much smaller than a VEC and a conventional single equation ECM suggests. Furthermore, the proposed model outperforms both others in respect of its forecasting power.
Keywords: 330; Kointegration; Kointegration; Modellierung; Zeitreihenanalyse; Schätzung; Privater Konsum; USA